53=-7-4n

Simple and best practice solution for 53=-7-4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 53=-7-4n equation:



53=-7-4n
We move all terms to the left:
53-(-7-4n)=0
We add all the numbers together, and all the variables
-(-4n-7)+53=0
We get rid of parentheses
4n+7+53=0
We add all the numbers together, and all the variables
4n+60=0
We move all terms containing n to the left, all other terms to the right
4n=-60
n=-60/4
n=-15

See similar equations:

| 4(y-2)+7=23 | | 2.x-1÷5=12 | | -4=-5+p/15 | | 9j-6j=3 | | -9+8k=-145 | | 8x+4=4x-1-7 | | -17m=-377 | | 3/5x-5=3/4x-2 | | 4x=11x^{2}. | | 16(14-4x)-10=6 | | x+2.25(x)=3/14 | | 2x-10=44+6 | | 5(2h-4)-3h=29 | | 2z/7+1=-4 | | |2x+7|=5 | | -17m=#377 | | (3x–3)/2=x+1   | | 3x|4-2=7 | | 2z/7+1=4 | | 6+9v=-156 | | 1/2x-2/3=1/4 | | 6k-12-3k=-6 | | 3/17=u/9 | | 49=3y+10 | | -3x-7=3-x | | 2/x^2=1/x^2-1/x | | 8/2=24/x | | 4/7z+2/7z=13 | | 6=v+3 | | 25t^2-20t-12=0 | | 2(j-65)=44 | | z/7+3=4 |

Equations solver categories